Proverbs, Ecclesiastes, Song of Songs - Murphy, Roland E. (Roland Edmund), 1917-2002.; Huwiler, Elizabeth, 1952- (Peabody, Mass. : Hendrickson Publishers ; Carlisle, Cumbria [UK] : Paternoster Press, 1999)
The New International Biblical Commentary offers the best of contemporary scholarship in a format that both general readers and serious students can use with profit. Based on the widely used New International Version translation, the NIBC presents careful section-by-section exposition with key terms and phrases highlighted and all Hebrew transliterated. A separate section of notes at the close of each chapter provides additional textual and technical comments. Each commentary also includes a selected bibliography as well as Scripture and subject indexes.
Proverbs / Roland E. Murphy -- Introduction: Proverbs. Introductory Instructions (Prov. 1:1-9:18). The Proverbs of Solomon (Prov. 10:1-22:16). The Sayings of the Wise (Prov. 22:17-24:34). The Proverbs of Solomon (Prov. 25:1-29:27). The Sayings of Agur (Prov. 30:1-14). Numerical Sayings (Prov. 30:15-33). The Sayings of Lemuel (Prov. 31:1-9). The Ideal Wife (Prov. 31:10-31) -- Ecclesiastes / Elizabeth Huwiler -- Introduction: Ecclesiastes -- Song of Songs / Elizabeth Huwiler -- Introduction: Song of Songs.
"Based on the New International version.".
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries; Bible -- Commentaries